KEKUASAAN PRODUKTIF AMERIKA SERIKAT DAN KONVENSI PERUBAHAN IKLIM PASCA PARIS AGREEMENT - Fadhlan Nur Hakiem (UNIDA Gontor, 2018)
The research aims at understanding the influence of the productive power of the United States on United Nations Convention on Climate Change (UNFCCC) after Paris Agreement. United States is the second largest contributor to greenhouse gas emissions in the world. Furthermore, the responsibility of the United States to participate in resolving climate change issues is expected. The decision of the United States to withdraw from the Paris Agreement is a step backwards to resolve the problem of climate change. Productive power of United States can disrupt the effectiveness of the UNFCCC. The research can be categorized as a qualitative research done through process tracing technique. The data were collected by literature study. The result of this research shows that the productive power of the United States makes UNFCCC dependon the United States and influences the behaviour of Convention member.